Killing two enemies with one stone? Genomics of resistance to two sympatric pathogens in Norway spruce. Issue 18 (5th August 2021) - Capador‐Barreto, Hernán D.; Bernhardsson, Carolina; Milesi, Pascal; Vos, Ingrid; Lundén, Karl; Wu, Harry X.; Karlsson, Bo; Ingvarsson, Pär K.; Stenlid, Jan; Elfstrand, Malin
Abstract: Trees must cope with the attack of multiple pathogens, often simultaneously during their long lifespan. Ironically, the genetic and molecular mechanisms controlling this process are poorly understood. The objective of this study was to compare the genetic component of resistance in Norway spruce to Heterobasidion annosum s . s . and its sympatric congener Heterobasidion parviporum . Heterobasidion root‐ and stem‐rot is a major disease of Norway spruce caused by members of the Heterobasidion annosum species complex. Resistance to both pathogens was measured using artificial inoculations in half‐sib families of Norway spruce trees originating from central to northern Europe. The genetic component of resistance was analysed using 63, 760 genome‐wide exome‐capture sequenced SNPs and multitrait genome‐wide associations. No correlation was found for resistance to the two pathogens; however, associations were found between genomic variants and resistance traits with synergic or antagonist pleiotropic effects to both pathogens. Additionally, a latitudinal cline in resistance in the bark to H. annosum s . s . was found; trees from southern latitudes, with a later bud‐set and thicker stem diameter, allowed longer lesions, but this was not the case for H. parviporum . In summary, this study detects genomic variants with pleiotropic effects which explain multiple disease resistance from a genic level and could be useful for selection of resistant trees to both pathogens. Furthermore, it highlights the need for additional research to understand the evolution of resistance traits to multiple pathogens in trees.